Grains of truth 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Grains of truthCommenting on the article 'Grains of truth' on genetic modification in Spore 88, our faithful correspondent Samuel Zeleke in Gambella, Ethiopia, writes: 'In most ACP States especially in Africa, agricultural research has been...